The two-stage processing of judgment of confidence: evidence from ERP - Zhaolan Li; Wenwu Dai; Ning Jia (BMC Psychology)
Abstract Background The judgment of confidence (JOC) refers to the confidence in the accuracy of the target item individuals have just retrieved and is a typical retrospective metacognitive monitoring process. In the classical paradigm of JOC, JOC occurs after the recognition or recall task. While initially viewed as a single-stage monitoring process, recent research on JOC suggests its internal mechanisms may be more complex, potentially encompassing both retrieval and monitoring processes. This study aims to delve into these mechanisms concerning neural temporal processes. Methods In this study, event-related potential (ERP) was used to compare N400 and slow-wave ERPs of high and low JOCs at different time windows using a classic JOC paradigm. Results Behavioral results showed an inverted-U shaped relationship between response time (RT) and JOCs, peaking at magnitude 3 before declining. There were significantly longer RT for low JOCs compared with high JOCs, along with lower recognition scores. The ERP results showed that low JOCs induced larger N400 in the right frontal lobe and right central area, while high JOCs induced larger slow-wave components (500 ~ 700ms) in the right frontal lobe. Conclusions Based on these findings, the present study suggests that JOC involves two processing stages. N400 reflects the process of cue acquisition, while the slow-wave component reflects the process of cue application. Furthermore, a two-stage model was proposed and validated, enriching the study of metacognition monitoring mechanisms, offering insights into the processing mechanisms of retrospective metacognitive monitoring.